Thromboembolism and antithrombotic therapy for heart failure in sinus rhythm - Lip, Gregory Y. H.; Ponikowski, Piotr; Andreotti, Felicita; Anker, Stefan D.; Filippatos, Gerasimos; Homma, Shunichi; Morais, Joao; Pullicino, Patrick; Rasmussen, Lars H.; Marin, Francisco; Lane, Deirdre A.; McMurray, J.; Hoes, A.; Ten Berg, J.; De Caterina, R.; Kristensen, S. D.; Zeymer, U. (Thrombosis and Haemostasis, 2012)
Chronic heart failure (HF) with either reduced or preserved left ventricular (LV) ejection fraction is common and remains an extremely serious disorder with a high mortality and morbidity. Many complications related to heart failure can be related to thrombosis. Epidemiological and pathophysiological data also link HF to an increased risk of thrombosis, leading to the clinical consequences of sudden death, stroke, systemic thromboembolism and/or venous thromboembolism. This executive summary of a joint consensus document of the Heart Failure Association (EHFA) of the European Society of Cardiology (ESC) and the ESC Working Group on Thrombosis reviews the published evidence, summarises ‘best practice’, and puts forward consensus statements that may help to define evidence gaps and assist management decisions in everyday clinical practice. In HF patients with atrial fibrillation, oral anticoagulation is clearly recommended, and the CHA2DS2-VASc and HAS-BLED scores should be used to determine the likely risk-benefit ratio (thromboembolism prevention versus risk of bleeding) of oralnticoagulation. In HF patients with reduced LV ejection fraction who are in sinus rhythm there is no evidence of an overall benefit of vitamin K antagonists (e.g. warfarin) on mortality, with risk of major bleeding. Whilst there is the potential for a reduction in ischaemic stroke, there is currently no compelling reason to routinely use warfarin for these patients. Risk factors associated with increased risk of thromboembolic events should be identified and decisions regarding use of anticoagulation individualised. Patient values and preferences are important determinants when balancing the risk of thromboembolism against bleeding risk. Novel oral anticoagulants that offer a different risk-benefit profile compared with warfarin may appear as an attractive therapeutic option, but this would need to be confirmed in clinical trials.Note: The editorial process for this article was fully handled by Prof. Christian Weber, Editor in Chief.
Keywords: Heart failure; sinus rhythm; thromboembolism; antithrombotic therapy; warfarin; aspirin